Faktor-Faktor yang Mempengaruhi Ibu dalam Pemberian Imunisasi DPT-HB-HIB pada Anak Di Posyandu Mawar Indah 11 Desa Babakan - Yolanda, Silvia; Nurhidayah, Siti Rahmah; Mardhatillah, Innana; Oktobriariani, Rona Riasma (Jurnal Sehat Mandiri, 2023)
According to the profile of the Bogor District Health Office in 2016, diphtheria is still a serious problem in Indonesia, especially in West Java, and in 2017, an outbreak of diphtheria occurred in Bogor District. This study aims to determine the factors that influence mothers in giving DPT-HB-Hib immunization to children. This research used a cross sectional approach which was carried out by researchers in the form of questions through questionnaires and interviews. The analysis used is univariate analysis and bivariate analysis. The population is all mothers who have toddlers with a sample size of 55 people. Data processing was carried out using computerization and statistical analysis of data using the chi-square test. The statistical test results obtained a p value of 0.001 ≤ 0.05, which means that there is a relationship between knowledge and DPT-HB-Hib immunization. Obtained a p value of 0.006 ≤ 0.05, which means that there is a relationship between education and DPT-HB-Hib immunization. Obtained a p value of 0.015 ≤ 0.05, which means there is a relationship between work and DPT-HB-Hib immunization. The p value is 0.000 ≤ 0.05. The conclusion in this study is that there is a relationship between information sources and DPT-HB-Hib immunization. It is recommended to be more proactive in seeking information to increase mother's knowledge about the importance of complete basic immunization, especially DPT-HB-Hib immunization in infants.